1987
DOI: 10.1111/j.1745-4557.1987.tb00819.x
|View full text |Cite
|
Sign up to set email alerts
|

RELATIONSHIP OF USDA QUALITY GRADES TO PALATABILITY OF COOKED BEEF1

Abstract: Prime carcasses produced loin and round steaks that were more palatable (P < 0.05) than were those from carcasses of Choice through Canner (7grades) in 85.7% of comparisons and from carcasses of Choice through Standard (3 grades) in 69.0% of comparison; comparable percentages were 71.4% (6 grades) and 42.9% (2 grades) for Choice and 74.3 96 (5 grades) and 35.7% (I grade) for Good. Among Prime through Standard carcasses, grade predicted flavor, tenderness and overall palatability of loin steaks with 30 to 38% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 23 publications
3
49
1
1
Order By: Relevance
“…Previous studies (Dolezal et al 1982;Tatum et al 1982;Smith et al 1983) did not find any differences in juiciness, amount of connective tissue, myofibrillar and overall tenderness, flavour desirability, and overall desirability with the range of grade fat and intramuscular fat content (Table 4) found in the present study. Several studies (Prior et al 1977;Burson et al 1980;Dikeman et al 1986;Miller et al 1987) found no effect of dietary energy content on palatability attributes of beef.…”
Section: Resultscontrasting
confidence: 30%
“…Previous studies (Dolezal et al 1982;Tatum et al 1982;Smith et al 1983) did not find any differences in juiciness, amount of connective tissue, myofibrillar and overall tenderness, flavour desirability, and overall desirability with the range of grade fat and intramuscular fat content (Table 4) found in the present study. Several studies (Prior et al 1977;Burson et al 1980;Dikeman et al 1986;Miller et al 1987) found no effect of dietary energy content on palatability attributes of beef.…”
Section: Resultscontrasting
confidence: 30%
“…Marbling is a visual score given to a piece of meat whereas IMF is the chemically measured fat content (includes membrane lipids) although the terms are often used interchangeably. Early work from the USA showed that higher levels of marbling were associated with improved palatability in cooked beef (McBee, Jr. & Wiles, 1967;Smith, Savell, Cross, Carpenter, Murphey & Aalhus, 1987) although generally marbling degree accounts for only 3-10% of the variation in sensory tenderness of beef (Nishimura et al, 1999). There has been extensive debate about the contribution that intramuscular fat makes to the sensory attributes of meat (Hocquette et al, 2010;Oddy et al, 2001).…”
Section: Effects Of Intramuscular Fat (Imf)mentioning
confidence: 99%
“…(4) Coefficients of determination for USDA marbling score (by scores and percentages with scores) for flavour, juiciness, tenderness and overall palatability in A + B carcasses were 27, 20, 26 and 33%, respectively, for loin steaks and 4, 20, 7 and 7% for top round steaks, respectively. Smith et al (1983) said:…”
Section: Palatability Prediction Using Usda Quality Gradesmentioning
confidence: 99%
“…Smith (2005) composited data from the studies of Smith et al (1980Smith et al ( , 1983Smith et al ( , 1984Smith et al ( , 1987, Branson et al (1984Branson et al ( , 1986, Savell et al (1987), Jones and Tatum (1991a, 1991b, Huffhines et al (1992aHuffhines et al ( , 1992bHuffhines et al ( , 1993 and George et al (1999) and concluded that the odds of having an unpleasant eating experience are 1 in 33 (3%) if a middle-meat steak comes from a prime carcass, as compared with 1 in 10 (10%), 1 in 6 (16%), 1 in 4 (27%) or 1 in 2 (50%) if a middle-meat steak comes from a carcass of upper two-thirds choice, lower one-third choice, select or standard grades, respectively. Platter et al (2003b) reported that: (i) marbling score displayed a significant relationship to acceptance of steaks by consumers; and (ii) the shape of the predicted probability curve for steak acceptance was approximately linear over the entire range of marbling scores (TR 67 to SA 97 ), suggesting that the likelihood of consumer acceptance of steaks increases~10% for each full marbling score increase between SL and SA.…”
Section: Palatability Prediction Using Usda Quality Gradesmentioning
confidence: 99%